2021
DOI: 10.1016/j.ejca.2021.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Younger age at onset of colorectal cancer is associated with increased patient’s delay

Abstract: This study aimed to investigate if younger age at diagnosis of colorectal cancer was associated with a diagnostic delay. The secondary objective was to evaluate if symptomatology varied with age. Method: The study population consisted of the cohorts from two prospective multicentre studies conducted in Sweden and Denmark, the QoLiRECT and QoLiCOL studies. These studies investigated the quality of life in patients with colorectal cancer. Participants responded to the validated questionnaires used to extract inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…The result is consistent with some quantitative studies indicating younger CRC patients were associated with increased likelihood of psychological distress [6,24]. A possible explanation for this is that younger patients may be more likely to disregard symptoms of CRC as they perceive themselves to be healthy, leading to maladaptation to the sick role and delay in diagnosis [25]. It has been reported that the probability of a long patient's delay and late stage was increased in CRC patients 60 years or younger, who still work may be less prone to seek medical advice due to lack of time.…”
supporting
confidence: 90%
“…The result is consistent with some quantitative studies indicating younger CRC patients were associated with increased likelihood of psychological distress [6,24]. A possible explanation for this is that younger patients may be more likely to disregard symptoms of CRC as they perceive themselves to be healthy, leading to maladaptation to the sick role and delay in diagnosis [25]. It has been reported that the probability of a long patient's delay and late stage was increased in CRC patients 60 years or younger, who still work may be less prone to seek medical advice due to lack of time.…”
supporting
confidence: 90%
“…CRC is the third most common malignant cancer with the second highest mortality rate ( Ayerden et al, 2021 ; Rydbeck et al, 2021 ; Peng et al, 2022 ). By applying CLAM to multi-omics data of CRC (see ‘Data collection and preprocessing’) with KNN ranging from 5 to 15, we obtained 88, 71, 59, 49, 42, 37, 35, 28, 27, 25 and 23 gene modules.…”
Section: Resultsmentioning
confidence: 99%
“…38 In younger patients, there may be delays by either patient or health care provider to report/investigate lower GI symptoms due to the higher likelihood of these resulting from less significant benign pathology. 39 Alternatively, recent studies have shown that earlyonset colorectal cancer is increasing in incidence and associated with adverse outcomes suggesting more aggressive disease characteristics that may predispose to emergency presentation. [40][41][42] Within the present study, both OS and CSS were analyzed.…”
Section: Discussionmentioning
confidence: 99%